Acemannan-based films: an improved approach envisioning biomedical applications - Rodrigues, Luísa Cidália Guimarães (2019)
In the last years, a renewed interest in natural compounds from medicinal plants uses arose due totheir intrinsic bioactive properties. Acemannan(ACE), aloe vera leaves the main polysaccharide, iscytocompatible, wound healing inducer, antibacterial and immunomodulator. Thus, its associationwith natural polymers as chitosan(CHT)and alginate(ALG)can result in strong synergistic effects,due to the interactions established between the polymers leading to mixed junction zones formation.In this work, ACE-basedfilms were prepared through the combination of ACE with CHT or ALG.Films were characterized to evaluate their physical features and chemical composition. Thefindingsrevealed that the presence of calcium ions into ACE composition induced an effective gelation withALG and a polymeric arrangement with CHT. Moreover, an increase of ACE ratio in ALG/ACE leadto more resistant and stable structures. Thefindings obtained suggest that ACE-basedfilms are goodcandidates to be used as bioactive platforms.